Plasma concentrations of cefazolin in pediatric patients undergoing cardiac surgery - Saowaphak Lapmahapaisan (2022)
Background: The guideline for antibiotic prophylaxis in pediatric cardiac surgery is currently unavailable, and the effects of cardiopulmonary bypass (CPB) may result in low plasma cefazolin concentrations and subsequent postoperative surgical site infections (SSIs). Aims: To demonstrate the calculated-unbound plasma concentrations of cefazolin during uncomplicated pediatric cardiac surgery. Settings and Design: A prospective observational study that included 18 patients <seven years of age, undergoing elective cardiac surgery with CPB. Materials and Methods: An intravenous infusion of cefazolin (25 mg.kg-1) was administered to patients over 30 minutes within 1 hour before skin incision (first dose). Another 25 mg.kg-1infusion was administered to the CPB prime volume (second dose). Blood samples were obtained at eight time points: 15 minutes after the first dose (T1); before aortic cannulation (T2); immediately after CPB initiation (T3); 30 (T4), 60 (T5), and 120 (T6) minutes after CPB; 15 minutes after CPB discontinuation (T7), and at skin closure (T8). The total plasma cefazolin concentrations were measured using liquid chromatography tandem mass spectrometry. Results: The unbound cefazolin concentrations were calculated assuming 80%-protein binding. The median cefazolin levels were 18.1 (range 4.3-27.0), 11.9 (2.8-24.1), 31.4 (18.3-66.1), 23.4 (13.7-35.9), 20.2 (15.4-24.9), 17.7 (14.8-18.0), 15.6 (9.8-26.2), and 13.3 (8.3-24.6) μg.mL-1from T1-T8, respectively. The cefazolin levels remained four times above the minimum inhibitory concentrations (MICs) for Methicillin-sensitive S. aureus (MSSA) and S. epidermidis in most patients, but they were inadequate for Enterobacter and E. coli. Conclusion: This regimen produced adequate plasma cefazolin concentrations for common organisms that cause SSIs after cardiac surgery.